2020
DOI: 10.11646/zootaxa.4834.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological types of spermatheca in Coreidae: bearing on intra-familial classification and tribal-groupings (Hemiptera: Heteroptera)

Abstract: The morphology of the spermatheca is described in 109 species of 86 genera representing all four currently recognised subfamilies of Coreidae, covering the undivided Hydarinae, both tribes of Pseudophloeinae, all three tribes of Meropachyinae and 27 of the 32 tribes of Coreinae. Three types of spermatheca are recognised. Type I is bipartite, consisting only of a simple tube differentiated into distal seminal receptacle and proximal spermathecal duct and lacks the intermediate part present in most Pentatomomorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Within the Coreoidea, recent phylogenomic results recovered Hydarinae and Pseudophloeinae as clades nested within the Alydidae, resulting in a rejection of the monophylies of both Alydidae and Coreidae (Forthman et al., 2019). This hypothesis is further supported by a recent morphological study of coreoid spermatheca (Pluot‐Sigwalt & Moulet, 2020) and the metathoracic scent gland peritreme (Hemala et al., 2021). Therefore, the higher classification of Coreoidea should be revised, with two equally sound alternative solutions: (i) incorporating Alydidae into a broadly defined Coreidae; or (ii) transferring Hydarinae and Pseudophloeinae into Alydidae sensu lato .…”
Section: Discussionsupporting
confidence: 58%
“…Within the Coreoidea, recent phylogenomic results recovered Hydarinae and Pseudophloeinae as clades nested within the Alydidae, resulting in a rejection of the monophylies of both Alydidae and Coreidae (Forthman et al., 2019). This hypothesis is further supported by a recent morphological study of coreoid spermatheca (Pluot‐Sigwalt & Moulet, 2020) and the metathoracic scent gland peritreme (Hemala et al., 2021). Therefore, the higher classification of Coreoidea should be revised, with two equally sound alternative solutions: (i) incorporating Alydidae into a broadly defined Coreidae; or (ii) transferring Hydarinae and Pseudophloeinae into Alydidae sensu lato .…”
Section: Discussionsupporting
confidence: 58%
“…Coreinae has repeatedly been recovered as paraphyletic with regards to Meropachyinae and based upon the typical Meropachyinae leg morphology we expect these fossil coreids do not fall within this clade but likely somewhere else within the Coreinae (Forthman et al 2019(Forthman et al , 2020Kieran et al 2019). Review of spermatheca within Coreidae by Pluot-Sigwalt and Moulet (2020) found that Hydarinae and Pseudophloeinae are morphologically unique but that Coreinae and Meropachyinae were similar, adding credibility to phylogenetic results which don't recover Coreinae and Meropachyinae as unique (Kieran et al 2019;Forthman et al 2019Forthman et al , 2020.…”
Section: Systematic Paleontologymentioning
confidence: 79%
“…Based on our examinations of specimens of these two tribes, Manocoreini has the following characteristics that are significantly different from the latter: (1) head with a small dentate or plate-like process in front of antenniferous tubercles, whereas without such process in Gonocerini ; (2) plica of female sternum VII with triangular, or rectangular depression, covered by sternum VI, whereas the posterior margin of plica depressed and near the anterior margin of sternum VII in Gonocerini ; (3) genital capsule has median ventroposterior process, whereas the posterior margin of genital capsule concave in Gonocerini ; (4) basiconjunctivum moderately sclerotized, whereas strongly sclerotized in Gonocerini . According to recent seminal research on the morphology of spermatheca in Coreidae ( Pluot-Sigwalt and Moulet 2020 ), the spermatheca of coreids was divided into three types (I, II, III), and type III could be subdivided into four subtypes (A, B, C, D). Based on our study, the spermatheca of Manocoreini belongs to type III, subtype A, and is closely related to Dasynini , Gonocerini , and Homoeocerini .…”
Section: Discussionmentioning
confidence: 99%
“…Photographs of the genitalic structures were taken using a Canon EOS 7D Mark II camera equipped with a LAOWA 25 mm F2.8 macro 2.5–5× macro lens, or equipped with a tube lens and a Mitutoyo M Plan Apo 10× objective lens. Morphological terminology follows Hsiao (1964) , Ren (1993) , Brailovsky (2007a , b ), Yi and Bu (2015) , Zhou and Rédei (2020) , and Pluot-Sigwalt and Moulet (2020) .…”
Section: Materials and Methodsmentioning
confidence: 99%